The Battle of the Factions - Pryor, Geoff, 1944- (1984)
The Hawke Government becomes unstuck when it attempts to introduce an assets test for tne old-age pension. Pragmatism prevails and it backs down in the face of community pressure.-- Information provided by Geoff Pryor.
Published in the Canberra Times on 23 February 1984.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Elections -- Australia -- Caricatures and cartoons; Australia -- Politics and government -- 1976-1990 -- Caricatures and cartoons